2005
DOI: 10.1530/eje.1.01871
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inhibin A and B, estradiol and follicle growth dynamics during ovarian stimulation in normo-ovulatory women

Abstract: Objective: To investigate the relationship between serum concentrations of inhibin A, inhibin B and estradiol (E 2 ) and the number of developing follicles during the administration of exogenous follicle-stimulating hormone (FSH) in various regimens in normo-ovulatory volunteers and to evaluate if inhibins act as suitable markers for the number of developing follicles during ovarian stimulation. Design and methods: Serial hormone determinations and assessment of follicle numbers were carried out during unstim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
(40 reference statements)
1
13
0
2
Order By: Relevance
“…No significant correlations were observed between the studied dynamic variables and pregnancy outcomes. This finding was consistent with earlier reports (5)(6)(7)(8).…”
Section: Figuresupporting
confidence: 94%
See 1 more Smart Citation
“…No significant correlations were observed between the studied dynamic variables and pregnancy outcomes. This finding was consistent with earlier reports (5)(6)(7)(8).…”
Section: Figuresupporting
confidence: 94%
“…Eldar-Geva et al (7) suggested that luteal phase E 2 with GnRH agonist long protocol is higher in high responders than in normal or poor responders. Hohmann et al (8) revealed that mid-and latefollicular phase levels of E 2 during ovarian stimulation without GnRH analogue were positively correlated with the number of follicles of different size categories in the late follicular phase. The present study was conducted in GnRH antagonist cycles, which differentiates it from earlier studies.…”
Section: Figurementioning
confidence: 99%
“…In addition, the differences were observed in the number of follicles <17 mm, which contribute less to the serum concentrations of oestradiol (Bomsel-Helmreich et al, 1979;van Dessel et al, 1996). However follicles <11 mm contribute more to circulating concentrations of inhibin B (Hohmann et al, 2005;Wen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it widely is considered that selection of the dominant follicle is impaired in women with PCOS, because of failure of FSH-dependent follicle recruitment (26). Apparently, by administration of a small amount of exogenous FSH, the ''blocked'' cyclic recruitment in women with PCOS can be overruled and multiple follicles surpass the FSH threshold (27). Despite this prolonged survival of follicles with continuous low-dose FSH administration after cyclic recruitment, development of a single dominant follicle was unaffected in the majority of treated PCOS subjects, as reflected by mono-ovulation.…”
Section: Discussionmentioning
confidence: 99%